1901 N.C. Sess. Laws 338-39 - (:unkn) unknown (My University, 1901)
Priv. Laws, ch. 124, § 14.: That among the powers conferred upon the Commissioners are the following: . . . to control the manner in which dynamite, blasting powder, gunpowder and other explosives and highly inflammable and dangerous substances may be stored and sold[.]
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER